Moninaisuus työelämässä ja johtamisessa - erityisherkät persoonat työssä - Ollila, Seija; Kujala, Anne (Hallinnon tutkimuksen seura, 2020)
Diversity in working life and leadership – High sensitive individuals at work Labor productivity and well-being are prerequisites for working life. The prerequisite for productivity is to find work meaningful, which has a direct impact on well-being at work. Meaningfulness is linked to the possibility and willingness to organize work and act in a way that suits you. Taking into account different personalities and utilizing know-how supports the experience of individual meaningfulness and creativity in the organization. Personal diversity, which is also understood as difference, is a scant consideration in organizations and management of work communities. Empirically implemented qualitative research is centered on a highly sensitive personality. Research questions focused on how diversi-ty-sensitive personality is reflected in working life, how individual work-related sensitivity should be taken into account at work and what kind of competence based management or leadership are needed? The survey was target-ed at the members of the Finnish Association for High Sensitive Person’s (HSP) Association (N = 944) in the autumn 2018. The analysis was performed by data-driven content analysis and by using quantification of the data. The lack of understanding of high sensitivity and intuitive abilities, practices, and needs of a person with a particular sensitivity to work revealed key findings. A highly sensitive person as an employee and a leader acts with strong empathy and emotional intelligence. She or he is heavily burdened by a poor working atmosphere and lack of appreciation. The highly sensitive person needs a peaceful working environment and a acceptance of diversity. Training and knowledge about high sensitivity is needed in working life and management.
Keywords: diversity; working life; leadership; high sensitive person; well-being at work; qualitative-quantitative research; työelämä; johtaminen; persoonallisuuden piirteet; työyhteisöt; temperamentti; herkkyys (psykologia); sosiaaliset taidot; introversio; persoonallisuus; luonteenpiirteet; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|